Practical Social Investigation : qualitative and quantitative methods in social research - Pole, Christopher; Lampard, Richard (Harlow : Prentice Hall, 2002)
This work is an invaluable source of knowledge for all students entering the field of social research. The book presents the basics of doing social research through an integrated approach, combining both qualitative and quantitative research methods.
Includes bibliographical references and index.
Keywords: Social sciences -- Research -- Methodology